Tandem mass tag-based quantitative proteomics analyses of a chicken-original virulent and its attenuated Histomonas meleagridis strain in China - Chen, Qiao-Guang; Zhang, Yu-Ming; Chen, Chen; Wang, Shuang; Li, Zai-Fan; Hou, Zhao-Feng; Liu, Dan-Dan; Tao, Jian-Ping; Xu, Jin-Jun (Frontiers in Veterinary Science, 2023)
Introduction Histomonas meleagridis can cause histomonosis in poultry. Due to the prohibition of effective drugs, the prevention and treatment of the disease requires new strategies. Questions about its pathogenic mechanisms and virulence factors remain puzzling. Methods To address these issues, a tandem mass tag (TMT) comparative proteomic analysis of a virulent strain and its attenuated strain of Chinese chicken-origin was performed. Results A total of 3,494 proteins were identified in the experiment, of which 745 proteins were differentially expressed (fold change ≥1.2 or ≤0.83 and p < 0.05), with 192 up-regulated proteins and 553 down-regulated proteins in the virulent strain relative to the attenuated strain. Discussion Surface protein BspA like, digestive cysteine proteinase, actin, and GH family 25 lysozyme were noted among the proteins up regulated in virulent strains, and these several proteins may be directly related to the pathogenic capacity of the histomonad. Ferredoxin, 60S ribosomal protein L6, 40S ribosomal protein S3, and NADP-dependent malic enzyme which associated with biosynthesis and metabolism were also noted, which have the potential to be new drug targets. The up-regulation of alpha-amylase, ras-like protein 1, ras-like protein 2, and involucrin in attenuated strains helps to understand how it is adapted to the long-term in vitro culture environment. The above results provide some candidate protein-coding genes for further functional verification, which will help to understand the molecular mechanism of pathogenicity and attenuation of H. meleagridis more comprehensively.